Changes in amount and intensity of physical activity over time in breast cancer survivors - Marell, Paulina S; Vierkant, Robert A; Olson, Janet E; Herrmann, Joerg; Larson, Nicole L; Lebrasseur, Nathan K; D’Andre, Stacy D; Ehlers, Diane K; Stan, Daniela L; Cheville, Andrea L; Barksdale, Toure; Loprinzi, Charles L; et al. (JNCI cancer spectrum, 2023)
Abstract Background Physical activity is associated with decreased breast cancer recurrence and mortality, as well as fewer treatment-related symptoms. Nevertheless, most breast cancer survivors do not meet physical activity guidelines. The purpose of this manuscript is to characterize physical activity trends over time in breast cancer survivors. Methods Mayo Clinic Breast Disease Registry participants received surveys at baseline and at 1 and 4 years after diagnosis; breast cancer recurrence and/or metastatic disease were exclusion criteria. Participants were considered to be meeting guidelines if they self-reported at least 150 minutes of moderate-intensity (eg, fast walking) and/or strenuous (eg, jogging) physical activity per week. Statistical analyses include analysis of covariance methods, paired t tests, conditional logistic regression models, and McNemar tests of homogeneity. Results A total of 171 participants were included in the analysis. The amount of total physical activity decreased over time (P = .07). Mild-intensity physical activity (eg, easy walking) decreased most over time (P = .05). Among participants aged 18-49 years, mild-intensity (P = .05) and moderate-intensity (P = .02) physical activity decreased over time. Strenuous-intensity physical activity levels decreased over time among participants with a normal body mass index (P = .002) and with obesity (P = .01). Conclusions We found a trend-level decrease in total physical activity over time, driven mostly by a decrease in mild-intensity physical activity. Young breast cancer survivors are especially likely to reduce their physical activity over time. Further research on implementing physical activity guidelines in clinical practice is warranted.